Proceedings of the Workshop on Speech and Natural Language - HLT '90 1990
DOI: 10.3115/116580.116641
|View full text |Cite
|
Sign up to set email alerts
|

Automatic phonetic baseform determination

Abstract: Phonetic baseforms are the basic recognition units in most large vocabulary speech recognition systems. These baseforms are usually determined by hand once a vocabulary is chosen and not modified thereafter. However, many applications of speech recognition, such as dictation transcription, are hampered by a fixed vocabulary and require the user be able to add new words to the vocabulary. At least one phonetic baseform must be assigned to each new word to properly integrate the word into the recognition system.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 11 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…Of particular interest to this work, are instances in which spoken examples are used to refine pronunciations [25]- [29]. The work of [27], for example, deduces a pronunciation given a word or grapheme sequence and an utterance of the spoken word . This research uses a decision tree to model which was later shown to produce poor results when compared to graphone models on L2S tasks.…”
Section: Related Workmentioning
confidence: 99%
“…Of particular interest to this work, are instances in which spoken examples are used to refine pronunciations [25]- [29]. The work of [27], for example, deduces a pronunciation given a word or grapheme sequence and an utterance of the spoken word . This research uses a decision tree to model which was later shown to produce poor results when compared to graphone models on L2S tasks.…”
Section: Related Workmentioning
confidence: 99%
“…Out-of-vocabulary (OOV) words are the bottleneck in largevocabulary open-domain speech recognition systems [1] and text-to-speech systems [2]. In order to solve the problem of OOV words, Grapheme-to-phoneme (g2p) conversion, which is structured learning problems for which there are an extremely large number of candidate answers, has been used for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…There has been significant research on automatic lexical generation [5,6,7]. However, the novel contribution of this work is two-fold: (1) Spoken examples of both the spelling and the word are used as opposed to the word only, and (2) a bi-directional L2S model is used to exchange bias information between the spelling and pronunciation domain so as to boost the overall performance of the tandem model.…”
Section: Introductionmentioning
confidence: 99%